Pengaruh Harga Jual dan Saluran Distribusi terhadap Volume Penjualan Kartu Perdana By.U Telkomsel pada CV. Sinar Telekom (Transputer) Lahat - Fytaloka, Vemi; Mujari; Pratiwi, Dini (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
This research aims to examine the influence of selling price and distribution channels on the sales volume of By.U starter packs at CV Sinar Telekom (Transputer) Lahat. The data analysis method used is quantitative using multiple linear regression, where the model equation is Y = a + b1X1 + b2X2 + eThe results of the t test analysis show that the selling price (X1) has a significant effect on sales volume (Y), while the distribution channel (X2) does not have a significant effect on buying interest (Y) for Telkomsel cards at CV. Sinar Telekom Lahat. Furthermore, the F test shows that simultaneously, selling price (X1) and distribution channel (X2) have a significant effect on sales volume interest (Y).. Conclusion, this research contributes to the understanding of the factors that influence the sales volume of Telkomsel cards in a specific business environment. The implications of the results of this research can be used as the basis for a more effective marketing strategy to increase interest in purchasing By.U Telkomsel starter cards in the local market. Keywords: Selling Price, Distribution Channels, Sales Volume